2007
DOI: 10.1186/1751-0147-49-28
|View full text |Cite
|
Sign up to set email alerts
|

Application of a zona pellucida binding assay (ZBA) in the domestic cat benefits from the use of in vitro matured oocytes

Abstract: Background: Zona pellucida binding assays (ZBAs) have proven useful in determining the fertilising ability of spermatozoa in several species. Most ZBAs use fresh or salt-stored oocytes collected from fresh ovaries but because ovaries are not easy to obtain on a regular basis, chilled and frozen-thawed ovaries have been tested, with varying results. The present study tested the hypothesis that cat spermatozoa, either fresh or frozen-thawed, can bind to homologous zona pellucida of oocytes retrieved from frozen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Our data confirm previous findings that porcine immature and in vitro-matured oocytes have a more porous net-like structure than the more compact surface of in vivo-matured oocytes [88]. Similarly, some studies showed that oocyte maturation is accompanied by changes in the ZP structure in human [30], mouse [31], and cat [32]. These changes may be relevant in the process of binding and penetration of spermatozoa into the ZP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data confirm previous findings that porcine immature and in vitro-matured oocytes have a more porous net-like structure than the more compact surface of in vivo-matured oocytes [88]. Similarly, some studies showed that oocyte maturation is accompanied by changes in the ZP structure in human [30], mouse [31], and cat [32]. These changes may be relevant in the process of binding and penetration of spermatozoa into the ZP.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we compared the composition and structure of the equine and porcine ZP as follows: 1) we identified the glycoproteins that comprise the equine and porcine ZP, 2) we described their localization in the ZP in both species using confocal fluorescence microscopy, and 3) we analyzed the morphological structure of the equine and porcine ZP using transmission and scanning electron microscopy. Moreover, earlier studies [30][31][32] have indicated that the ZP could be modified during maturation. Therefore, we analyzed immature, in vitro-matured, and in vivo-matured oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in vitro redefinition of the approach resulted in more conflicting outcomes. In our study the use of fresh in vitro matured oocytes was adopted, as the beneficial use of IVM oocytes for application of ZP-binding assay has been reported in different species (Marco-Jiménez & Vicente 2004;Hermansson et al, 2007) as also supported by the fact that mature and immature oocytes differ in the glycoproteins of the zona pellucida, along with the number of sperm receptors (Lucas et al, 2003). By contrast Braundmeier and colleagues (2002) in vitro competitive zona binding assay could rank the bulls, but did not correlate with the 56day no return rates, zona binding in vivo, or the number of accessory spermatozoa detected on in vivo produced embryos.…”
Section: Discussionmentioning
confidence: 99%
“…ZBA has been studied in dogs (Hermansson, Ponglowhapan, Forsberg, & Holst, ) as well as in cats (Hermansson, Axnér, & Holst, ). The interaction between spermatozoa and the ZP is a critical event resulting in fertilization and reflects multiple sperm functions (i.e.…”
Section: Review Of Sperm Functional Testsmentioning
confidence: 99%
“…ZBA has been studied in dogs (Hermansson, Ponglowhapan, Forsberg, & Holst, 2006) as well as in cats (Hermansson, Axnér, & Holst, 2007).…”
Section: Zona Pellucida Binding Assay (Zba)mentioning
confidence: 99%